Wpływ pochodzenia kaczek z różnych stad zachowawczych na wybrane cechy jakościowe jaj - Okruszek, Andrzej; Książkiewicz, Juliusz; Haraf, Gabriela; Biernat, Jadwiga (Influence of the Ducks' Origin from Different Conservative Flocks on the Selected Qualitative Traits of Eggs, 2008)
The objective of the study was to compare chemical composition and fatty acids profile of eggs of two-year old light type ducks - Orpington (O1) and crossbreed ducks Khaki Campbell×Orpington (KhO) as well as Pekin type ducks - P9, A1 and A2 from conservative flocks, collected at the start - the 6th week of second laying period. There were no significant differences in the moisture (in egg white and yolk), cholesterol content in yolk lipids and pH value of egg white in the investigated eggs. The eggs of A1, A2 and P9 comprised of more (P≤0.05; P≤0.01) protein in egg white (11.01%, 10.97% and 10.85% respectively) and yolk (16.34%, 16.26% and 16.24% respectively) than O1 and KhO eggs (10.74% and 16.07% as well as 10.66% and 16.21% respectively). Furthermore the A2 eggs were characterized by the lowest of lipids' content in yolk (27.19% v/s 29.45- 30.99%) and pH yolk value (6.27 v/s 6.31-6.40). In P9, A1 and A2 eggs, yolk lipids contained more palmitic (C 16:0), eicosapentaenoic (C 20:5 n-3 - EPA), docasatetraenoic (C 22:4 n-6) and docosahexaenoic (C 22:6 n-3 - DHA) and less CLA 18:2 n-6 and trans isomer fatty acids (C 16:1 trans-9 and C 18:1 trans-11) than those of O1 and KhO eggs. The unsaturated fatty acids (UFA) were predominant in yolk lipids of eggs for all flocks (69.02%-72.28%). The A1 yolk lipids contained the most of UFA, polyunsaturated fatty acids - PUFA (19.74%) and saturated fatty acid - SFA (27.41%). A higher concentration of PUFA from n-6 group was observed in A1 (15.42%) and KhO (15.32%) eggs. Eggs yolks collected from P9, A1 and A2 ducks were characterized by higher level of n-3 PUFA (4.34%, 4.32% and 4.71% respectively) in comparison to KhO and O1 eggs (3.97% and 4.10% respectively). (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 43-50